MENGHIDUPKAN INGATAN (KOLEKTIF) AKTIVISME JAKARTA KAIGUN BUKANFU SELAMA PENDUDUKAN JEPANG DI INDONESIA DALAM KOLEKSI NISHIJIMA: Array - Arief Rahman Bramantya (Jurnal Kearsipan, 2017)
This study provides an explanation of the archival works conducted by Waseda University specifically in the Nishijima Collection. The collection contains historical resources about the Japanese occupation in Indonesia in relation with Jakarta Kaigun Bukanfu. The Nishijima collection has become the “historical heritage” in the development of science and knowledge. This study discusses about Jakarta Kaigun Bukanfu in the Nishijima Collection with the historical perspective in an attempt to explore the historiography of Indonesia. By doing the research, it appears that archives hold valuable information. Jakarta Kaigun Bukanfu is an organization founded by the Rear Admiral Tadashi Maeda. Through the archival research and comprehensive analysis of the Nishijima Collections, it is concluded that this organization is generally expected to regulate the relationship between two regions and their authorities, to organize the defense and security, to conduct trade protection, to conduct a survey of Natural Resources and Human Resources, to prepare the procurement of ammunition, transportation arrangements, counterespionage and intelligence activities. However, when the Japanese was almost defeated by the Allied, some members of this organization did desertion. The activity of some members of the organization reflected their special bargaining position in front of Maeda. It showed especially in the establishment of Asrama Indonesia Merdeka.